Characteristics of the Attentional Network in Children with Sleep-Disordered Breathing - Wu Y; Wang Y; Wang C; Zhao F; Ma D; Xu Z; Ni X (Nature and Science of Sleep, 2023)
Yunxiao Wu,1 Yan Wang,2,3 Changming Wang,4 Fujun Zhao,5 Dandi Ma,6 Zhifei Xu,6,7 Xin Ni5,7 1Beijing Key Laboratory of Pediatric Diseases of Otolaryngology, Head and Neck Surgery, Beijing Pediatric Research Institute, Beijing Children’s Hospital, Capital Medical University, National Center for Children’s Health, Beijing, People’s Republic of China; 2Center on Aging Psychology, CAS Key Laboratory of Mental Health, Institute of Psychology, Beijing, People’s Republic of China; 3Department of Psychology, University of Chinese Academy of Sciences, Beijing, People’s Republic of China; 4Department of Neurosurgery, Xuanwu Hospital, Capital Medical University, Beijing, People’s Republic of China; 5Department of Otolaryngology, Head and Neck Surgery, Beijing Children’s Hospital, Capital Medical University, National Center for Children’s Health, Beijing, People’s Republic of China; 6Respiratory Department 1, Beijing Children’s Hospital, Capital Medical University, National Center for Children’s Health, Beijing, People’s Republic of China; 7MOE Key Laboratory of Major Diseases in Children, Beijing Children’s Hospital, Capital Medical University, National Center for Children’s Health, Beijing, People’s Republic of ChinaCorrespondence: Zhifei Xu, Respiratory Department 1, Beijing Children’s Hospital, Capital Medical University, National Center for Children’s Health, 56 Nanlishi Road, Xicheng, Beijing, 100045, People’s Republic of China, Tel +8613521660077, Email zhifeixu@aliyun.com Xin Ni, Department of Otolaryngology, Head and Neck Surgery, Beijing Children’s Hospital, Capital Medical University, National Center for Children’s Health, 56 Nanlishi Road, Xicheng, Beijing, 100045, People’s Republic of China, Tel +8613370115099, Email nixin@bch.com.cnPurpose: To explore the characteristics of the attentional network and related factors in children with sleep-disordered breathing (SDB).Patients and Methods: A total 228 children (200 children aged 6– 10 years with snoring or mouth breathing, admitted to our hospital from May 2020 to July 2022, and 28 healthy children recruited from the community as the control group) were enrolled. All participants underwent polysomnography (PSG) and completed the ADHD rating scale and child version of the Attention Network Test. According to their SDB history and obstructive apnea hypopnea index (OAHI), the participants were divided into control (n = 28), primary snoring (PS; n = 67) and obstructive sleep apnea (OSA; n = 133) groups.Results: The OSA and PS groups were younger than controls (P < 0.05). The proportion of boys was higher in the OSA than control group (P < 0.05). Body mass index was higher in the OSA than control and PS groups (P < 0.01). Attention deficit and hyperactive impulsivity scores were independently associated with the OAHI (P < 0.001). The efficiency of the alerting network was higher in the OSA than in controls (P = 0.020), but was not correlated with OAHI after adjusting for age, sex and SDB history duration (P > 0.05).Conclusion: Children with OSA have impaired attention, characterized by excessive alerting network activation. However, alerting network efficiency did not change linearly with disease severity. More research is needed to elucidate the neural mechanisms underlying attention deficits in pediatric OSA.Keywords: child, obstructive sleep apnea, attention, alerting network